SLFN11 expression correlates with immune microenvironment and predicts prognosis in melanoma - Zeng, Huancheng; Chen, Guishan; Fang, Yutong; Wu, Jundong; Jiang, Qiongzhi; Zhang, Rendong (Frontiers in Immunology, 2025)
BackgroundSchlafen family member 11 (SLFN11) has been implicated in cancer biology and immune modulation, but its expression patterns, prognostic value, and role in tumor immunity in melanoma remain incompletely defined.MethodsThrough multi-omics analyses of public databases (The Human Protein Atlas, TIMER2, BEST) and functional validation, we characterized SLFN11 in melanoma. Functional assays were conducted in SLFN11-overexpressing melanoma cells to evaluate effects on M0 macrophage polarization, recruitment of macrophages and CD8⁺ T cells, and CD8⁺ T cell cytotoxic activity.ResultsSLFN11 mRNA levels are reduced in skin cutaneous melanoma (SKCM) compared to normal skin, yet higher in metastatic lesions than in primary tumors. High SLFN11 expression correlates with favorable overall and progression-free survival across multiple independent melanoma cohorts, with consistent prognostic value across clinical subgroups (tumor stages, nodal/metastatic status). Multivariable Cox regression analysis, adjusting for factors like gender, age, and pathologic T/N/M stages, confirmed SLFN11 expression as an independent predictor of favorable overall survival. SLFN11 expression associates with enhanced infiltration of immune cells along with co-expression of immune checkpoint molecules. Furthermore, SLFN11 expression is associated with favorable prognosis in immunotherapy-treated patients. Functional assays show that SLFN11-overexpressing melanoma cells promote M0 macrophage polarization toward an M1 phenotype, enhance recruitment of macrophages and CD8⁺ T cells, and slightly increase CD8⁺ T cell cytotoxic activity.ConclusionsThese findings provide evidence that SLFN11 is associated with immune microenvironment changes in melanoma, correlates with favorable prognosis, and may be linked to immunotherapy response, supporting its potential as a candidate biomarker and therapeutic target for further investigation.